PROJETO EXTENSÃO INDUSTRIAL EXPORTADORA - PEIEX: RESULTADOS DA RELAÇÃO UNIVERSIDADE, EMPRESA E GOVERNO - Silva, Schana S.; Burkhard, Michele T.; Rochinheski, Denise; Bonfada, Anderson; Ferreira, Glaci B.; Kuhn, Ivo N. (Salão do Conhecimento, 2013)
Resumo